2018
DOI: 10.1038/s41386-018-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflaming sex differences in mood disorders

Abstract: Men and women often experience different symptoms or rates of occurrence for a variety of mood disorders. Many of the symptoms of mood disorders overlap with autoimmune disorders, which also have a higher prevalence in women. There is a growing interest in exploring the immune system to provide biomarkers for diagnosis of mood disorders, along with new targets for developing treatments. This review examines known sex differences in the immune system and their relationship to mood disorders. We focus on immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 289 publications
(310 reference statements)
2
51
0
Order By: Relevance
“…Related to this point, chronic intoxication activated inflammatory signaling and cell death pathways in female but not male mice, and confirmation studies showed that ethanol dependent females exhibited significant neuronal degeneration in cortical regions, whereas cell death in males was significantly reduced ( Hashimoto and Wiren, 2008 ; Wilhelm et al, 2015 ). Finally, a broader implication of the current findings is pertinent to sex differences in the immune system and the relationship to mood disorders (reviewed in Rainville and Hodes, 2018 ). Taken in conjunction with sex differences in mood and anxiety disorders (e.g., Altemus et al, 2014 ), future studies examining potential immune or stress-related mechanisms that may contribute to stress and ethanol susceptibility and associated mood disorders will be important.…”
Section: Discussionmentioning
confidence: 93%
“…Related to this point, chronic intoxication activated inflammatory signaling and cell death pathways in female but not male mice, and confirmation studies showed that ethanol dependent females exhibited significant neuronal degeneration in cortical regions, whereas cell death in males was significantly reduced ( Hashimoto and Wiren, 2008 ; Wilhelm et al, 2015 ). Finally, a broader implication of the current findings is pertinent to sex differences in the immune system and the relationship to mood disorders (reviewed in Rainville and Hodes, 2018 ). Taken in conjunction with sex differences in mood and anxiety disorders (e.g., Altemus et al, 2014 ), future studies examining potential immune or stress-related mechanisms that may contribute to stress and ethanol susceptibility and associated mood disorders will be important.…”
Section: Discussionmentioning
confidence: 93%
“…Compared to males, female patients reported greater decrease in HRQL despite having a similar self-reported severity of the disease [15]. Although not yet fully understood, sex differences regarding mood disorders might be related not only to hormonal differences but also to diversities in the immune system [16]. Women show higher numbers of innate and adaptive immune cells and have a higher incidence of disorders associated with an increased immune response such as autoimmune diseases and allergies [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…These findings demonstrate striking sex differences in the persistent changes in basal gene expression after a subchronic immune challenge. (Importantly, this suggests that differential vulnerability to cognitive decline, memory impairments, and affective disorders (Himanen et al, 2006;Hogue et al, 2003;Lavoie et al, 2017;Léveillé et al, 2017;Liossi et al, 2009;Niemeier et al, 2007;Rainville and Hodes, 2018;Suarez et al, 2015) after illness or injury may be mediated by sex differences in the changes in gene expression and transcriptional regulation that persist long after immune challenge.…”
Section: Discussionmentioning
confidence: 99%
“…These sex-specific patterns of enduring changes in gene expression after subchronic immune challenge are consistent with strikingly different patterns of gene expression in the brain of males and females after stress or drugs of abuse (Hodes et al, 2015;Mychasiuk et al, 2016;Finn et al, 2018;Randesi et al, 2018), and further demonstrate that environmental insults have sex-specific implications for enduring changes in gene expression, neural function, and vulnerability to subsequent stressors. Such sex differences in transcriptional regulation may also provide new insights into differential vulnerability to cognitive decline, memory impairments, and affective disorders (Hogue et al, 2003;Liossi and Wood, 2014;Rainville and Hodes, 2019).…”
Section: Discussionmentioning
confidence: 99%